Odorant Binding Protein C17 Contributes to the Response to Artemisia vulgaris Oil in Tribolium castaneum - Gao, Shan-Shan; Li, Rui-Min; Xue, Shuang; Zhang, Yuan-Chen; Zhang, Yong-Lei; Wang, Jing-Shun; Zhang, Kun-Peng (Frontiers in Toxicology, 2021)
The red flour beetle, Tribolium castaneum (T. castaneum), generates great financial losses to the grain storage and food processing industries. Previous studies have shown that essential oil (EO) from Artemisia vulgaris (A. vulgaris) has strong contact toxicity to larvae of the beetle, and odorant-binding proteins (OBPs) contribute to the defense of larvae against A. vulgaris. However, the functions of OBPs in insects defending against plant oil is still not clear. Here, expression of one OBP gene, TcOBPC17, was significantly induced 12–72 h after EO exposure. Furthermore, compared to the control group, RNA interference (RNAi) against TcOBPC17 resulted in a higher mortality rate after EO treatment, which suggests that TcOBPC17 involves in the defense against EO and induces a declining sensitivity to EO. In addition, the tissue expression profile analysis revealed that the expression of TcOBPC17 was more abundant in the metabolic detoxification organs of the head, fat body, epidermis, and hemolymph than in other larval tissue. The expression profile of developmental stages showed that TcOBPC17 had a higher level in early and late adult stages than in other developmental stages. Taken together, these results suggest that TcOBPC17 could participate in the sequestration process of exogenous toxicants in T. castaneum larvae.